Elevated serum preptin concentrations in patients with diabetic nephropathy. (9th June 2019) - Wang, Rui; Xue, Aili; Zheng, Wenjian; Wang, Linchuan; Yan, Fei; Hu, Wenchao; Lin, Jingna; He, Lanjie
Abstract : Preptin is a peptide synthesized and secreted accompanied with insulin from pancreatic β cells. Here, we tested the hypothesis that serum preptin concentrations are correlated with diabetic nephropathy (DN). Our study was performed in a population of 234 patients with type 2 diabetes mellitus (T2DM) and 78 healthy subjects. Patients with T2DM were divided into three groups: normoalbuminuria group (DN0, n=106), microalbuminuria group (DN1, n=90), and macroalbuminuria group (DN2, n=38) according to urine albumin to creatinine ratio (ACR). Serum preptin concentrations were significantly increased in the three T2DM subgroups than those in the controls. DN2 group showed significantly higher serum preptin concentrations compared with DN0 and DN1 groups. Moreover, DN1 group had higher serum preptin concentrations than DN0 group. Serum preptin was correlated with a higher risk of T2DM and DN after logistic regression analysis. Simply linear regression analysis demonstrated a positive correlation between serum preptin and gender, body mass index (BMI), blood urea nitrogen, creatinine, ACR, and a negative correlation between serum preptin and glomerular filtration rate, metformin, acarbose treatment. Gender, BMI, and ACR were still positively correlated with serum preptin after multiple linear regression analysis. Our findings indicate that serum preptin concentrations are associated with renal function and DN.